Evaluating steady-state resting energy expenditure using indirect calorimetry in adults with overweight and obesity. Issue 7 (July 2020) - Popp, C.J.; Butler, M.; Curran, M.; Illiano, P.; Sevick, M.A.; St-Jules, D.E.
Summary: Background: Determining a period of steady state (SS) is recommended when estimating resting energy expenditure (REE) using a metabolic cart. However, this practice may be unnecessarily burdensome and time-consuming in the research setting. Aim: The aim of the study was to evaluate the use of SS criteria, and compare it to alternative approaches in adults with overweight and obesity. Methods: In this cross-sectional, ancillary analysis, participants enrolled in a bariatric (study 1; n = 13) and lifestyle (study 2; n = 51) weight loss intervention were included. Indirect calorimetry was performed during baseline measurements using a metabolic cart for 25 min, including a 5-min stabilization period at the start. SS was defined as the first 5-min period with a coefficient of variation (CV) ≤10% for both VO2 and VCO2 (hereafter REE5–SS ). Body composition was measured using bioelectrical impedance analysis in study 2 participants only. REE5–SS was compared against the lowest CV (REECV–lowest ), 5-min time intervals (REE6–10, REE11–15, REE16–20, REE21–25 ), 4-min and 3-min SS intervals (REE4–SS and REE3–SS ), and time intervals of 6–15, 6–20 and 6–25 min (REE6–15, REE6–20, and REE6–25 ) using repeated measures ANOVA and Bland–Altman analysis to test for bias, limits of agreement and accuracy (±6% measured REE). Results: Participants were 54 ± 13 years old, mostly women (75%) and had a BMI of 35 ± 5 kg/m 2 . Overall, 54/63 (84%) of participants reached REE5–SS, often (47/54, 87%) within the first 10-min (6–15 min). Alternative approaches to estimating REE had a relatively low bias (−16 to 13 kcals), narrow limits of agreement and high accuracy (83–98%) when compared to REE5–SS, in particular, outperforming standard prediction equations (e.g., Mifflin St. Joer). Conclusion: Indirect calorimetry measurements that utilize the 5-min SS approach to estimate REE are considered the gold-standard. Under circumstances of non-SS, it appears 4-min and 3-min SS periods, or fixed time intervals of atleast 5 min are accurate and practical alternatives for estimating REE in adults with overweight and obesity. However, future trials should validate alternative methods in similar populations to confirm these findings.